Pomiędzy propaganda a kolaboracją: casus Getto Cajtung - Polit, Monika (Zagłada Żydów. Studia i Materiały, 2006)
This article deals with the establishment and the brief history of the only official newspaper in the Łódź Ghetto. The author focuses primarily on a few selected themes and analyses them in terms of style and language, which leads her to classify the discourse of the Geto-Cajtung as one of propaganda. The quotations from the press and relevant commentaries demonstrate the role of the newspaper's propaganda discourse in the shaping of a favourable image of the “Elder” of Łódź Ghetto Jews – Mordechaj Rumkowski.